Large-scale grid-connected renewable energy in Australia: Potential barriers, strategies and policy support mechanisms that may affect RE development from the perspective of energy specialists at a leading consultancy operating in the built environment in Australia - Campbell, Benjamin (Department of Construction Economics and Management, 2021)
Barriers to renewable energy development in the past have been identified as high upfront costs with challenges around equity and debt financing, as well as limited legal frameworks and limited regulatory support. Although it is noted that barriers to development are country specific, as well as the solutions to overcome such barriers. Policy measures implemented in various countries to support renewable energy have been seen to have a marked impact on its development. The renewable energy industry in Australia is showing unprecedented growth with a drastic change in the energy landscape expected in the future, should all proposed developments come to fruition. Renewable energy in Australia is currently in its infancy though. It is expected that the planned integration of all the proposed developments in the National Electricity Market will result in certain barriers to development emerging at higher levels of integration. Australia's energy policy has taken significant steps to supporting the deployment of cleaner generation technologies, although hurdles at federal and state level have in the past frustrated the development of renewable energy. The history and status quo of renewable energy development in Australia has been investigated. The current framework and support structures in place as well as potential barriers have been reviewed. A qualitative investigation utilising a single case study approach was selected as the research method. The case investigated was the renewable energy division of a leading global engineering consultancy operating in Australia. The participants of the study included the senior management staff in the renewable energy division of the company. Standard open-ended interviews were conducted. The data was analysed by employing a method of pattern matching. The observed data from the interview process was analysed and compared against the expected pattern which had emerged from the literature. Potential barriers and support strategies have been outlined as a conclusion to the study. The study found federal energy policy to be favourable, but not vital for continued growth of RE development. It was acknowledged that a focus on grid infrastructure would be vital to avoid constricting asset development. The development of Renewable Energy Zones was considered a favourable strategy to overcoming barriers identified, although it was noted that community acceptance would be a significant consideration. Gas generation may form part of the future energy mix, but will be dependent on price and emergent technology. Pumped hydro power is expected to be an important compliment to renewable energy in future, to assist in addressing the technical barriers associated with high levels of non-synchronous generation in the network. A reform of the NEM may also be required to cater for a scenario of a significant penetration of renewable energy and is a topic recommended for future research.